Evaluasi Kelengkapan Resep Rawat Jalan Terhadap Standar Pelayanan Farmasi di Upt Puskesmas Ibrahim Adjie Kota Bandung - Nur Istiqomah, Fatihah; Eka Rusmana, Wempi (Cerdika: Jurnal Ilmiah Indonesia, 2022)
The importance of reviewing prescriptions to realize medication safety in pharmaceutical services. Good Pharmacy Practice (GPP) where the professional relationship between doctors and pharmacists is in the form of prescriptions as part of the representative quality of pharmaceutical service standards. The purpose of this study was to determine the percentage of administration on prescription completeness based on 3 aspects; administration, pharmaceutical and clinical to the percentage of pharmacy service standards at UPT. Ibrahim Adjie Health Center in Bandung City is adjusted to the PERMENKES RI No. 74 of 2016. This type of research is qualitative non-experimental descriptive observational with prospective data collection using a check list form to find out whether or not they fulfill each other in a recipe. This study was conducted in July 2021 with 150 samples of prescriptions for adult patients aged 26-45 years. The percentage of results from administrative screening was 10.6% or as many as 16 complete prescriptions due to not fulfilling the patient’s address, SIP and doctor’s initials. The percentage of pharmaceutical screening aspects obtained 58.6% or as many as 88 prescriptions that meet. The percentage of clinical screening showed 3.3% or as many as 5 prescriptions. Meanwhile, the results of the conformity of pharmaceutical services as a whole according to the applicable regulation of the Minister of Health indicate that there are no mutually fulfilling aspects in 1 prescription sheet. So the evaluation of this research needs to be done communication in increasing awareness between doctors and pharmacists in prescribing services as representatives of applicable service standards.